2023
DOI: 10.3389/fped.2023.1092548
|View full text |Cite
|
Sign up to set email alerts
|

Developing a nomogram for predicting surgical intervention in pediatric intussusception after hydrostatic reduction

Abstract: PurposeThe aim of this study was to develop and validate a nomogram for predicting surgical intervention in pediatric intussusception after hydrostatic reduction.MethodsChildren with intussusception who had treated with sonographically guided saline hydrostatic reduction as an initial treatment were enrolled in this study. The enrolled patients were randomly selected for training and validation sets, and the split ratio was 7:3. The medical records of enrolled patients were retrospectively reviewed. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…In contrast, the leukocyte count may not be considered as an independent risk factor. This finding contradicts the results of Zhuang et al’s study, 19 in which white blood cell count was found to be an independent risk factor but C-reactive protein was not. Chen et al’s 30 study also confirmed that in cases of intussusception in children, the C-reactive protein levels were significantly higher in patients who underwent enterectomy compared to those who did not.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In contrast, the leukocyte count may not be considered as an independent risk factor. This finding contradicts the results of Zhuang et al’s study, 19 in which white blood cell count was found to be an independent risk factor but C-reactive protein was not. Chen et al’s 30 study also confirmed that in cases of intussusception in children, the C-reactive protein levels were significantly higher in patients who underwent enterectomy compared to those who did not.…”
Section: Discussioncontrasting
confidence: 94%
“…They identified timing of onset, mass length, and history of infection as independent predictors. Similarly, Zhuang et al 19 retrospectively analyzed clinical data from 139 children who underwent hydrostatic reduction for intussusception and developed a preoperative nomogram using multiple logistic regression analysis. Their study identified several effective predictors including duration of symptoms, presence of blood in stool, white blood cells count, CK-MB levels, long axis diameter, ultrasound findings indicating adverse prognosis, and mental state of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results were consistent with the findings of previous studies, indicating that a longer duration of illness was more common in patients with intestinal necrosis ( 7 , 11 , 12 , 14 , 19 – 21 ). Longer duration of symptoms before presentation is related to an increase in the loss of intestinal viability ( 18 ).…”
Section: Discussionsupporting
confidence: 92%
“…Compared with screening for predicting risk factors for intestinal necrosis in pediatric intussusception as shown in previous studies (5,6,11,12), a nomogram integrates more variables and replaces complex statistical models with a simple and straightforward graph (13). Furthermore, in recent years, some researchers have expressed grave concern about the predictive ability of nomograms for intussusception and have stated their potential predictive utility (14,15). To our knowledge, there are few studies focusing on Abdominal pain, vomiting, and bloody stool constitute the classic triad of intussusception, but are presented in less than 33% of children upon admission (16).…”
Section: Discussionmentioning
confidence: 99%